Análise crítica do percentual de compensação ambiental aplicada para os empreendimentos potencialmente poluidores do Estado do Rio de Janeiro - Barros, Mariana de Almeida de (2011)
This paper aims to review the literature to demonstrate legal developments with regard to environmental compensation, since its creation by law 9.985/2000 to the present day. It will be presented the Terms of Appointment of Environmental Compensation signed between the entrepreneurs and the environmental agency of Rio de Janeiro, the State Environmental Institute (INEA), signed in 2009. The presentation of the facts in chronological order will aid understanding the current situation, where the undefinitions have created uncertainties for the entrepreneur about the value to be set for payment of non-mitigable impacts, as fragility of argument for the environmental agency. After reviewing the literature, including relevant legislation and the concepts of Environmental Economics, licensing and analysis conducted in 2009, it was concluded that the current methodology of calculation needs to be improved to achieve its main goal which is able to set compensation counteract the damage caused to the negative environmental settings